RELATIONSHIP BETWEEN PSYCHOLOGICAL FATIGUE AND WORK STRESS WITH PERFORMANCE AMONG MOTHERS WORKING AT ALASA PUBLIC HEALTH CENTER, NORTH NIAS REGENCY - Sinaga, Taruli Rohana; Sembiring, Rinawati; Munthe, Seri Asnawati; Sitorus, Mido Ester J; Hulu, Enjel Siska Dewita (Jurnal Ilmiah Keperawatan, 2026)
Working mothers in the health sector, particularly in community health centers, face the challenge of playing dual roles as professionals and homemakers. This situation has the potential to cause psychological fatigue and work stress, which can impact their performance. This study aims to analyze the relationship between psychological fatigue and work stress on the performance of working mothers at the Alasa Public Health Center (PHC) in North Nias Regency. This study is a quantitative study with a cross-sectional design. The sample consisted of 36 married women working at the Alasa PHC. Data collection was conducted using a questionnaire that had been tested for validity and reliability. Data analysis was performed using univariate and bivariate analysis using the chi-square test. The results showed a significant relationship between psychological fatigue and performance with a p-value = 0.005 <α=0.05 and a significant relationship between work stress and performance with a p-value = 0.001 <α=0.05. Mothers who experienced psychological fatigue and high work stress tended to show low performance. This situation is exacerbated by heavy workloads, significant domestic responsibilities, particularly within the family environment, lack of rest time, and minimal social support. This study recommends managerial efforts to identify and manage psychological factors that affect working mothers, such as emotional support from superiors, colleagues, and family, adequate rest time, more flexible work schedules, and improved welfare. The implementation of these strategies is expected to reduce psychological fatigue and work stress, thereby significantly and measurably improving the performance of female health workers, particularly working mothers, which in turn will have a positive impact on overall performance.